(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The European Atlantic Ocean offers a high potential for marine renewable energy (MRE), which is targeted to be at least 32% of the EU’s gross final consumption by 2030. The European Commission is supporting the development of the ocean energy sector through an array of activities and policies: the Green Deal, the Energy Union, the Strategic Energy Technology Plan (SET-Plan) and the Sustainable Blue Economy Strategy. The nascent status of the MRE sector and Wave Energy (WE) in particular, yields many unknowns about its potential environmental pressures and impacts. Wave Energy Converters’ (WECs) operation in the marine environment is still perceived by regulators and stakeholders as a risky activity. The complexity of MRE licensing processes is also indicated as one of the main barriers to the development of the sector. The lack of clarity of procedures, the varied number of authorities to be consulted and the early stage of Marine Spatial Planning (MSP) implementation are examples of the issues identified that may delay the permitting of the projects. Finally, there is also a need to provide more information on the sector to the general public. Only with an informed society would be possible to carry out fruitful public debates on MRE implementation at the local level. These non-technological barriers that could hinder the future development of WE in EU were addressed by the WESE project funded by EMFF in 2018. The present project builds on the results of the WESE project and aims to move forward through the following specific objectives: • Development of an Environmental Research Demonstration Strategy based on the collection, processing, modelling, analysis and sharing of environmental data collected in WE sites from different European countries where WECs are currently operating (Mutriku power plant and BIMEP in Spain, Aguçadoura in Portugal and SEMREV in France). • Development of a Consenting and Planning Strategy through providing guidance to ocean energy developers and to public authorities tasked with consenting and licensing of WE projects in France and Ireland; this strategy will build on country-specific licensing guidance and on the application of the MSP decision support tools (i.e. WEC-ERA[1] and VAPEM[2] tools) developed for Spain and Portugal in the framework of the WESE project; the results will complete guidance to ocean energy developers and public authorities for most of the EU countries in the Atlantic Arch. • Development of a Public Education and Engagement Strategy to work collaboratively with coastal communities in France, Ireland, Portugal and Spain, to co-develop and demonstrate a framework for education and public engagement (EPE) of MRE enhancing ocean literacy and improving the quality of public debates. The project will finish in September 2023. In this contribution we present the main outcomes, results and lessons learnt during the project. [1] https://aztidata.es/wec-era/; [2] https://aztidata.es/vapem/